Effect of Age of Transplants on Fruit and Seed Yield of Tomato (Solanum lycopersicum L.) - Y R Shukla (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
Tomato is a major cash crop of the mid-hill regions of Himachal Pradesh. Among various factors that affect its growth and yield, age of the transplant - an important factor - is generally ignored by farmers. Therefore, the present investigation was undertaken at Vegetable Research Farm, Department of Vegetable Science, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, during the summer of 2008 and 2009 to ascertain optimum age of transplants for maximizing fruit and seed yield in tomato var. Solan Vajr. The experiment was laid out in RBD, with 3 replications. Age of the transplant starting with 15 days, and with subsequent gaps of 3 days each (upto 42 days, i.e., 10 stages) comprised different treatments. Among the various treatments imposed, 33-day old (middleaged) transplants performed best with respect to fruit and seed yield than younger or older transplants. This treatment also gave the best results for number of fruits per plant, fruit yield per plot (kg), seed recovery (%), seed yield per plot (g), and germination percentage.